Development of a Website-Based Online Queue Information System for Health Services: Pengembangan Sistem Informasi Antrian Berbasis Website untuk Layanan Kesehatan - Yasinta, Aulia Nur; Sumarno, Sumarno; Taurusta, Cindy; Findawati, Yulian (Indonesian Journal of Innovation Studies, 2023)
This research focuses on developing an information system to address the issue of long queues and patient discomfort in health services at hospitals or clinics. The study utilizes the waterfall method, applying sequential and systematic stages in software development. The result is an online queue information system accessed through a website, enabling patients to register online and view real-time doctor appointments from the comfort of their homes. The system aims to reduce waiting times and improve patient satisfaction in obtaining healthcare services. Highlights: Development of a website-based online queue information system to address queueing issues in health services. Utilization of the waterfall method in the sequential and systematic software development process. The system's positive impact on reducing waiting times and improving patient satisfaction in accessing healthcare services.